Corrosion method for displaying grain and structure of high alloy steel material together

CN119354663AActive Publication Date: 2025-01-24KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411516413.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-24
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The metallographic corrosion methods of existing high alloy steels are complex in operation and take a long time, making it difficult to simultaneously show grains and microstructure.

Method used

A specific corrosive agent is used to immerse and corrode the surface of polished high-alloy steel specimens. By adjusting the composition of the corrosive liquid and the immersion time, good microstructure and grain corrosion effects can be obtained simultaneously in a short time.

Benefits of technology

This method can clearly observe the alloy crystal and micro -tissue in different thermal treatment states. It is suitable for studying the grain appearance, grain size and micro -organization of high -alloy steel, simple operation steps, saving time and economic costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005106815550000011
    Figure HDA0005106815550000011
  • Figure HDA0005106815550000012
    Figure HDA0005106815550000012
  • Figure HDA0005106815550000021
    Figure HDA0005106815550000021
Patent Text Reader

Abstract

The invention relates to a corrosion method for displaying grains and tissues of a high-alloy steel material together, and belongs to the technical field of high-alloy steel metallographic corrosion. High alloy steel samples in different heat treatment process states are mechanically polished; the high-alloy steel sample subjected to mechanical polishing is subjected to mechanical polishing and then is sequentially cleaned through deionized water and ethyl alcohol, and a high-alloy steel metallographic sample is obtained through blow-drying; according to different heat treatment process states of the high-alloy steel sample, the high-alloy steel metallographic sample is soaked in a corrosive liquid to be corroded until dark gray corrosion rust stains appear on the surface of the high-alloy steel metallographic sample; the corrosive liquid is composed of concentrated hydrochloric acid, concentrated nitric acid, FeCl3 and absolute ethyl alcohol; a high-alloy steel metallographic sample corroded by the corrosive liquid is placed in deionized water, the surface of the sample is wiped by cotton until dark gray corrosion rust stains become dark silver, the sample is cleaned by absolute ethyl alcohol and dried, and the microstructure and grain morphology of the high-alloy steel sample are observed by a metallographic microscope.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a corrosion method for co-displaying crystal grains and structures of a high-alloy steel material, belonging to the technical field of metallographic corrosion of high-alloy steel. Background Art

[0002] High alloy steel is mainly used in mining machinery, transmission gears, bearings, high-speed cutting tools and other working scenes with complex service performance. With the application of science and technology and the needs of industrial production, the service environment is becoming more and more harsh, and higher requirements are put forward for high alloy steel. High alloy steel in special service environment is not only in high temperature, high impact and high fatigue state for a long time, but also often in a short instantaneous heating state. Therefore, high alloy steel should have good high temperature oxidation resistance, high dimensional stability, high high temperature hardness, good toughness and contact fatigue. In order to meet the performance requirements, this type of material usually has a high carbon content and a complex alloy element ratio, and the content of alloy elements is very high. Therefore, studying the microstructure of high alloy steel is of great significance to understanding the relationship between the composition, organization and performance of the alloy. However, due to its complex composition and special process state, the preparation of metallographic samples of this type of material under different process states is more complicated, and the grains and microstructures require different corrosive media to complete during the corrosion process. The commonly used methods for corrosion of high alloy steel grains and structures are as follows: (1) Use 1g KMnO4+90mL H2O+10mL concentrated sulfuric acid solution in a 60℃ water bath for 2h to perform grain boundary corrosion; (2) Use 2g CuCl2+50ml HCl+50ml H2O solution to corrode for 5s to observe carbides and matrix structure.

[0003] The above metallographic etching agents are relatively complicated to operate during the application process, and can only reveal the grains or microstructures of the experimental materials under heating or long-term corrosion conditions. Especially in terms of grain visualization, the operation is complicated and time-consuming, and the effects of corroding grains and structures cannot be achieved at the same time. Summary of the invention

[0004] In view of the technical problems that the corrosion conditions for the manifestation of high-alloy steel grains and microstructures are harsh and the grains and microstructures cannot be presented at the same time, the present invention proposes a corrosion method for the simultaneous manifestation of the grains and microstructures of high-alloy steel materials. By immersing and corroding the surface of a polished high-alloy steel sample with a specific corrosive agent, good microstructure and grain corrosion effects can be obtained simultaneously in a short time. After the high-alloy steel is corroded by the method of the present invention, the alloy grain boundaries and microstructures under different heat treatment states can be clearly observed, and the method is suitable for studying the grain morphology, grain size and microstructure of high-alloy steel under different heat treatment process states.

[0005] A corrosion method for high alloy steel material with both grain and structure showing, the specific steps are as follows:

[0006] (1) High alloy steel samples in different heat treatment process states are mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence; the heat treatment process state is quenching state, tempering state, or cold treatment state;

[0007] (2) mechanically polishing the mechanically ground high alloy steel sample, then washing it with deionized water and ethanol in turn, and drying it to obtain a high alloy steel metallographic sample;

[0008] (3) According to different heat treatment process states of the high alloy steel samples, the high alloy steel metallographic samples are immersed in a corrosive solution and corroded until dark gray corrosion rust stains appear on the surface of the high alloy steel metallographic samples; the corrosive solution is composed of commercially available concentrated hydrochloric acid, concentrated nitric acid, FeCl3 and anhydrous ethanol;

[0009] (4) The high-alloy steel metallographic specimens corroded by the corrosive liquid were placed under deionized water, and the surface of the specimens was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimens were then cleaned with anhydrous ethanol and blown dry, and the microstructure and grain morphology of the high-alloy steel specimens were observed using a metallographic microscope.

[0010] The alloy composition of the high alloy steel is as follows: in terms of mass percentage, the C content in the high alloy steel is 0.1-0.15%, the total content of alloy elements is 29-36%, the total content of impurity elements P and S is not more than 0.02%, and the rest is Fe.

[0011] Preferably, the specific method of mechanical polishing in step (2) is: using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm to perform mechanical polishing until the surface is mirror-like and there are no polishing marks in different directions under optical microscope observation.

[0012] The liquid-to-solid ratio of concentrated hydrochloric acid, concentrated nitric acid, FeCl3 and anhydrous ethanol in the etching solution of step (3) is 5-25:0.5-1:1-5:5-25.

[0013] The heat treatment process state of the high alloy steel sample is the quenching state, and the calculation formula of the corrosion time t of the high alloy steel metallographic sample after being immersed in the corrosive liquid is:

[0014] t = -1.25x + 11.42;

[0015] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0016] The heat treatment process state of the high alloy steel sample is the tempering state. The calculation formula of the corrosion time t of the high alloy steel metallographic sample immersed in the corrosive liquid is:

[0017] t = -1.25x + 21.42;

[0018] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0019] The heat treatment process state of the high alloy steel sample is the cold treatment state. The calculation formula of the corrosion time t of the high alloy steel metallographic sample immersed in the corrosive liquid is:

[0020] t = -1.25x + 16.42;

[0021] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium.

[0022] Preferably, in the step (3), the heat treatment process state of the high alloy steel sample is a quenched state, and the high alloy steel metallographic sample is immersed in a corrosive solution for 5 to 10 minutes;

[0023] The heat treatment process state of the high alloy steel sample is the tempering state, and the high alloy steel metallographic sample is immersed in the corrosive solution for 15 to 20 minutes;

[0024] The heat treatment process state of the high alloy steel sample is the cold treatment state, and the high alloy steel metallographic sample is immersed in the corrosive solution for 10 to 15 minutes.

[0025] The corrosion principle of high alloy steel material grain and organization: After quenching, the alloy elements of high alloy steel are almost all dissolved in the matrix martensite phase. During the corrosion process, the quenched martensite phase is relatively coarse, the atomic arrangement at the grain boundary is irregular and the free energy is high. - In acidic environments, grain boundaries and structures are easily corroded, which allows the grain boundaries and structures to appear in a shorter corrosion time; after deep cryogenic treatment, the martensite phase of high-alloy steel materials is refined and a small amount of fine precipitates are generated. During the corrosion process, the corrosion time is prolonged due to the dense structure; after tempering treatment, the high-alloy steel materials are further refined into tempered structure, which is different from quenched martensite and is accompanied by a large number of precipitates. The denser tempered structure and the mutual influence between different phases further prolong the corrosion time.

[0026] The beneficial effects of the present invention are:

[0027] (1) The present invention uses a specific corrosive agent to immerse and corrode the surface of a polished high-alloy steel sample for a specific period of time, thereby simultaneously obtaining good microstructure and grain corrosion effects in a short period of time;

[0028] (2) After the high alloy steel is corroded by the method of the present invention, the alloy grain boundaries and microstructures under different heat treatment conditions can be clearly observed, which is suitable for studying the grain morphology, grain size and microstructure of high alloy steel under different heat treatment process conditions;

[0029] (3) The method of the present invention has low requirements for the corrosive environment and simple operation steps, which effectively saves time and economic costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a 200-fold metallographic image of the quenched high alloy steel prepared in Example 1;

[0031] Figure 2 This is a 200-fold metallographic image of the quenched high alloy steel prepared in Example 2;

[0032] Figure 3 This is a 200-fold metallographic image of the quenched high alloy steel prepared in Example 3;

[0033] Figure 4 This is a 200-fold metallographic image of the tempered high alloy steel prepared in Example 4;

[0034] Figure 5 This is a 200-fold metallographic image of the tempered high alloy steel prepared in Example 5;

[0035] Figure 6 This is a 200-fold metallographic image of the tempered high alloy steel prepared in Example 6;

[0036] Figure 7 This is a 100-fold metallographic image of the cold-treated high-alloy steel prepared in Example 7;

[0037] Figure 8 This is a 100-fold metallographic image of the cold-treated high-alloy steel prepared in Example 8;

[0038] Fig. 9 This is a 100-fold metallographic image of the cold-treated high-alloy steel prepared in Example 9;

[0039] Fig.10 This is a 100-fold metallographic image of a high alloy steel prepared using the method of 1g KMnO4+90mL H2O+10mL concentrated sulfuric acid solution in Comparative Example 1;

[0040] Fig.11 This is a 500-fold metallographic image of high-alloy steel prepared using the 2g CuCl2+50ml HCl+50ml H2O solution method in Comparative Example 2. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0042] The alloy composition of the high alloy steel in the embodiment of the present invention is as follows: in terms of mass percentage, the C content in the high alloy steel is 0.1-0.15%, the total content of alloy elements is 29-36%, the total content of impurity elements P and S is not more than 0.02%, and the rest is Fe.

[0043] Example 1: A corrosion method for co-displaying grains and structures of high alloy steel materials, the specific steps are as follows:

[0044] (1) The quenched high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0045] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0046] (3) Calculating the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (quenching state) of the high alloy steel sample, wherein the corrosion solution consists of 5 mL of commercially available concentrated hydrochloric acid, 0.5 mL of concentrated nitric acid (mass concentration of 65%), 1 g of FeCl3 and 5 mL of anhydrous ethanol;

[0047] t = -1.25x + 11.42;

[0048] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0049] In this embodiment, t is 10.17 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 10.17 min. Dark grey corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0050] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0051] The 200-fold metallographic image of the quenched high alloy steel prepared in this embodiment is shown in Figure 1 ,from Figure 1 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0052] Example 2: A corrosion method for co-displaying grains and structures of a high alloy steel material, the specific steps are as follows:

[0053] (1) The quenched high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0054] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0055] (3) Calculating the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (quenching state) of the high alloy steel sample, wherein the corrosion solution consists of 15 mL of commercially available concentrated hydrochloric acid, 0.75 mL of concentrated nitric acid (mass concentration of 65%), 3 g of FeCl3 and 15 mL of anhydrous ethanol;

[0056] t = -1.25x + 11.42;

[0057] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0058] In this embodiment, t is 7.67 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 7.67 min. Dark grey corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0059] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0060] The 200-fold metallographic image of the quenched high alloy steel prepared in this embodiment is shown in Figure 2 ,from Figure 2 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0061] Example 3: A corrosion method for co-displaying grains and structures of a high alloy steel material, the specific steps are as follows:

[0062] (1) The quenched high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0063] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0064] (3) Calculating the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (quenching state) of the high alloy steel sample, wherein the corrosion solution consists of 25 mL of commercially available concentrated hydrochloric acid, 1 mL of concentrated nitric acid (mass concentration of 65%), 5 g of FeCl3 and 25 mL of anhydrous ethanol;

[0065] t = -1.25x + 11.42;

[0066] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0067] In this embodiment, t is 5.17 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 5.17 min. Dark grey corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0068] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0069] The 200-fold metallographic image of the quenched high alloy steel prepared in this embodiment is shown in Figure 3 ,from Figure 3 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0070] Example 4: A corrosion method for co-displaying grains and structures of a high alloy steel material, the specific steps are as follows:

[0071] (1) The tempered high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0072] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0073] (3) Calculating the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (tempered state) of the high alloy steel sample, wherein the corrosion solution consists of 5 mL of commercially available concentrated hydrochloric acid, 0.5 mL of concentrated nitric acid (mass concentration of 65%), 1 g of FeCl3 and 5 mL of anhydrous ethanol;

[0074] t = -1.25x + 21.42;

[0075] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0076] In this embodiment, t is 20.17 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 20.17 min. Dark gray corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0077] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0078] The 200-fold metallographic image of the tempered high alloy steel prepared in this embodiment is shown in Figure 4 ,from Figure 4 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0079] Example 5: A corrosion method for co-displaying grains and structures of high alloy steel materials, the specific steps are as follows:

[0080] (1) The tempered high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0081] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0082] (3) Calculating the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (tempered state) of the high alloy steel sample, wherein the corrosion solution consists of 15 mL of commercially available concentrated hydrochloric acid, 0.75 mL of concentrated nitric acid (mass concentration of 65%), 3 g of FeCl3 and 15 mL of anhydrous ethanol;

[0083] t = -1.25x + 21.42;

[0084] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0085] In this embodiment, t is 17.67 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 17.67 min. Dark gray corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0086] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0087] The 200-fold metallographic image of the tempered high alloy steel prepared in this embodiment is shown in Figure 5 ,from Figure 5 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0088] Example 6: A corrosion method for co-displaying grains and structures of a high alloy steel material, the specific steps are as follows:

[0089] (1) The tempered high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0090] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0091] (3) Calculating the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (tempered state) of the high alloy steel sample, wherein the corrosion solution consists of 25 mL of commercially available concentrated hydrochloric acid, 1 mL of concentrated nitric acid (mass concentration of 65%), 5 g of FeCl3 and 25 mL of anhydrous ethanol;

[0092] t = -1.25x + 21.42;

[0093] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0094] In this embodiment, t is 15.17 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 15.17 min. Dark gray corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0095] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0096] The 200-fold metallographic image of the tempered high alloy steel prepared in this embodiment is shown in Figure 6 ,from Figure 6 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0097] Example 7: A corrosion method for high alloy steel material with co-development of grains and structures (see Figure 1 ), the specific steps are as follows:

[0098] (1) The cryogenically treated high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0099] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0100] (3) Calculate the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (cryogenic treatment state) of the high alloy steel sample, wherein the corrosion solution consists of 5 mL of commercially available concentrated hydrochloric acid, 0.5 mL of concentrated nitric acid (mass concentration of 65%), 1 g of FeCl3 and 5 mL of anhydrous ethanol;

[0101] t = -1.25x + 16.42;

[0102] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0103] In this embodiment, t is 15.17 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 15.17 min. Dark gray corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0104] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0105] The 100x metallographic picture of the cryogenically treated high alloy steel prepared in this embodiment is shown in Figure 7 ,from Figure 7 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0106] Example 8: A corrosion method for co-displaying grains and structures of a high alloy steel material, the specific steps are as follows:

[0107] (1) The cryogenically treated high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0108] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0109] (3) Calculate the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (cryogenic treatment state) of the high alloy steel sample, wherein the corrosion solution consists of 15 mL of commercially available concentrated hydrochloric acid, 0.75 mL of concentrated nitric acid (mass concentration of 65%), 3 g of FeCl3 and 15 mL of anhydrous ethanol;

[0110] t = -1.25x + 16.42;

[0111] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0112] In this embodiment, t is 12.67 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 12.67 min. Dark grey corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0113] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0114] The 100x metallographic picture of the cryogenically treated high alloy steel prepared in this embodiment is shown in Figure 8 ,from Figure 8 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0115] Example 9: A corrosion method for high alloy steel material with co-development of grains and structures (see Figure 1 ), the specific steps are as follows:

[0116] (1) The cryogenically treated high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0117] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0118] (3) Calculate the corrosion time of the high alloy steel metallographic sample after immersion in the corrosion solution according to the heat treatment process state (cryogenic treatment state) of the high alloy steel sample, wherein the corrosion solution consists of 25 mL of commercially available concentrated hydrochloric acid, 1 mL of concentrated nitric acid (mass concentration of 65%), 5 g of FeCl3 and 25 mL of anhydrous ethanol;

[0119] t = -1.25x + 16.42;

[0120] Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium;

[0121] In this embodiment, t is 10.17 min. Therefore, the high alloy steel metallographic sample is immersed in the corrosive solution and corroded for 10.17 min. Dark grey corrosion rust stains appear on the surface of the high alloy steel metallographic sample.

[0122] (4) The high alloy steel metallographic specimen corroded by the corrosive liquid was placed in deionized water, and the surface of the specimen was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimen was then cleaned with anhydrous ethanol and dried, and the microstructure and grain morphology of the high alloy steel specimen were observed using a metallographic microscope;

[0123] The 100x metallographic picture of the cryogenically treated high alloy steel prepared in this embodiment is shown in Fig. 9 ,from Fig. 9 The clear microstructure and grain morphology of high alloy steel materials can be seen at the same time.

[0124] Comparative Example 1: High alloy steel metallographic corrosion method, the specific steps are as follows:

[0125] (1) The quenched high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0126] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0127] (3) The high alloy steel metallographic specimen was immersed in a corrosion solution for 2 hours; the corrosion solution consisted of 1 g KMnO4, 90 mL H2O and 10 mL commercially available concentrated sulfuric acid;

[0128] (4) The high alloy steel metallographic specimens corroded by the corrosive solution were cleaned with deionized water and anhydrous ethanol in turn and dried, and the microstructure and grain morphology of the high alloy steel specimens were observed using a metallographic microscope;

[0129] The 100x metallographic picture of the high alloy steel prepared in this comparative example is shown in Fig.10 ,from Fig.10 It can be seen that this etching method can only obtain the grain morphology but cannot reveal the microstructure, and the operation is complicated and time-consuming.

[0130] Comparative Example 2: High alloy steel metallographic corrosion method, the specific steps are as follows:

[0131] (1) The tempered high alloy steel sample was mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence;

[0132] (2) The mechanically polished high-alloy steel sample was mechanically polished using a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm until the surface was mirror-like and there were no polishing marks in different directions under optical microscope observation, and then washed with deionized water and ethanol in turn, and dried to obtain a high-alloy steel metallographic sample;

[0133] (3) The high alloy steel metallographic sample was immersed in a corrosion solution for 5 seconds; the corrosion solution consisted of 2g CuCl2, 50ml HCl (commercially available concentrated hydrochloric acid), and 50ml H2O;

[0134] (4) The high alloy steel metallographic specimens corroded by the corrosive solution were cleaned with deionized water and anhydrous ethanol in turn and dried, and the microstructure and grain morphology of the high alloy steel specimens were observed using a metallographic microscope;

[0135] The 500-fold metallographic picture of the high alloy steel prepared in this comparative example is shown in Fig.11 ,from Fig.11 It can be seen that this etching method can only obtain the microstructure but cannot reveal the grain morphology.

[0136] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A corrosion method for co-development of grains and structures of high alloy steel material, characterized in that: The specific steps are as follows: (1) High alloy steel samples in different heat treatment process states are mechanically polished with sandpaper of 360 mesh, 600 mesh, 800 mesh, 1000 mesh, and 2000 mesh in sequence; the heat treatment process state is quenching state, tempering state, or cold treatment state; (2) mechanically polishing the mechanically ground high alloy steel sample, then washing it with deionized water and ethanol in turn, and drying it to obtain a high alloy steel metallographic sample; (3) According to different heat treatment process states of the high alloy steel samples, the high alloy steel metallographic samples are immersed in a corrosive solution and corroded until dark gray corrosion rust stains appear on the surface of the high alloy steel metallographic samples; the corrosive solution is composed of concentrated hydrochloric acid, concentrated nitric acid, FeCl3 and anhydrous ethanol; (4) The high-alloy steel metallographic specimens corroded by the corrosive liquid were placed under deionized water, and the surface of the specimens was wiped with cotton until the dark gray corrosion stains turned into dark silver. The specimens were then cleaned with anhydrous ethanol and blown dry, and the microstructure and grain morphology of the high-alloy steel specimens were observed using a metallographic microscope.

2. The corrosion method for co-development of grains and structures of high alloy steel material according to claim 1, characterized in that: The specific method of mechanical polishing in step (2) is: use a woolen polishing cloth and a diamond polishing paste with a particle size of 0.5 μm to perform mechanical polishing until the surface is mirror-like and there are no polishing marks in different directions under optical microscope observation.

3. The corrosion method for co-development of grains and structures of high alloy steel material according to claim 1, characterized in that: The liquid-to-solid ratio of concentrated hydrochloric acid, concentrated nitric acid, FeCl3 and anhydrous ethanol in the etching solution of step (3) is 5-25:0.5-1:1-5:5-25.

4. The corrosion method for co-development of grains and structures of high alloy steel material according to claim 1, characterized in that: Step (3) The heat treatment process state of the high alloy steel sample is the quenching state, and the calculation formula for the corrosion time t of the high alloy steel metallographic sample after being immersed in the corrosive liquid is: t = -1.25x + 11.42; Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium; The heat treatment process state of the high alloy steel sample is the tempering state. The calculation formula of the corrosion time t of the high alloy steel metallographic sample immersed in the corrosive liquid is: t = -1.25x + 21.42; Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium; The heat treatment process state of the high alloy steel sample is the cold treatment state. The calculation formula of the corrosion time t of the high alloy steel metallographic sample immersed in the corrosive liquid is: t = -1.25x + 16.42; Where, t is the corrosion immersion time, min; x is the mass fraction of FeCl3 in the corrosive medium.

5. The corrosion method for co-development of grains and structures of high alloy steel material according to claim 4, characterized in that: In step (3), the heat treatment process state of the high alloy steel sample is a quenched state, and the high alloy steel metallographic sample is immersed in a corrosive solution for 5 to 10 minutes; The heat treatment process state of the high alloy steel sample is the tempering state, and the high alloy steel metallographic sample is immersed in the corrosive solution for 15 to 20 minutes; The heat treatment process state of the high alloy steel sample is the cold treatment state, and the high alloy steel metallographic sample is immersed in the corrosive solution for 10 to 15 minutes.

Citation Information

Patent Citations

  • Metallographic corrosive agent for double-phase medium manganese steel and metallographic structure display method

    CN112857950A

  • Method for detecting grain boundary cementite of steel cord wire rod

    CN113970550A

  • 6082 aluminum alloy friction stir welding seam metallographic structure corrosion method

    CN116678712A

  • Metallographic display method of gallium arsenide polycrystal

    CN117451713A

  • Corrosion method for colored metallographic phase of aluminum alloy

    CN117571431A